THE EFFECT OF FINANCIAL AND NON-FINANCIAL REWARDS ON EXECUTIVES' PERFORMANCE IN MANUFACTURING FIRMS: A CASE STUDY AT KULIM-HI TECH PARK, KULIM, KEDAH, MALAYSIA - Bokhori Md Amin, (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
Compensation and benefits are one of the very important human resource management practices in addressing issues related to job performance. Therefore, the purpose of this study is to assess the extent of the role of financial and non-financial rewards and their contribution to the performance of executives in manufacturing firms. Methodology in this study was built where a questionnaire was designed for data collection to measure compensation and benefits related to financial and non-financial rewards on executives' performance. Data were collected among executives in manufacturing firms at Kulim Hi-tech Park, Kulim, Kedah, Malaysia which had a 4438 population, 351 samples, and 244 respondents successfully collected from 25 manufacturing firms. A stratified sampling method was used to determine the samples and the data obtained were analyzed using SmartPLS version 3.7.8. The finding of this study found that financial rewards have no significant relationship with executive job performance. While non-financial rewards have a significant relationship with executive job performance. It is proved from SmartPLS analysis shown that the financial rewards variable have a negative impact on executives' performance compared with non-financial rewards have a positive impact on executives' performance in manufacturing firms. The limitation of the study only covers the manufacturing firms. Another limitation is the respondents only included executives. Apart from these limitations, this study can give a strong impact on the top management of manufacturing firms to design the strategy of compensation and benefits which covered financial and non-financial rewards to be more effective in improving the work performance of executives.